The Effect of Work Overload and Work-Family Conflict on Job Embeddedness with Emotional Exhaustion as A Mediating Variable and Coworker Support as A Moderation Variable - Husaini Bachtiar; Praptini Yulianti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Nurses play a crucial role in the internal operations of the hospital, offering patients care, attention, assistance, and support. One of the most crucial things for hospitals to pay attention to is working hours since, if neglected, it will lead to nurses feeling under pressure at work, making it difficult for them to spend time with their families. If the two issues are properly handled, the employment attachment of nurses may also decline. This type of research method uses the quantitative explanation research method as a causal approach to the influence of work overload and work-family conflict on job embeddedness, with emotional exhaustion as a mediating variable and coworker support as a moderation variable in nurses at Islam PKU Muhammadiyah Hospital Tegal Regency. 96 inpatient nurses who responded to a questionnaire made up the study sample. SEM was used as the approach for data analysis in this investigation. According to the findings of this study, work stress and work-family conflict considerably impact emotional exhaustion. Furthermore, work overload, work-family conflict, and emotional exhaustion have no significant effect on job embeddedness. Additionally, the association between work overload and work-family conflict and job embeddedness is unaffected by emotional exhaustion as a mediator and co-worker support as a moderation variable.